Protective role of Liv.52 on the toxicity of acetaminophen during embryogenesis and postnatal development in wistar rats - D.P.SANTHOSH KUMAR,; M.DEECARAMAN,; M.VIJAYALAKSMI,; RAMESH EDAMULA,; H.KRISHNAPPA,; K. KAMALA,; VIJAYKUMAR B.MALASHETTY, (International Journal of Pharma and Bio Sciences, 2015)
Acetaminophen induced hepatic injury may also mediate its developmental toxic effects. The present study was carried out to evaluate the protective role of herbal hepato-protective formulation (Liv.52) against acetaminophen induced developmental toxicity in Wistar rats. Acetaminophen induced toxicity during embryogenesis and postnatal development was evaluated by administering daily doses of 500 or 1000 mg/kg/day through oral gavage starting from gestation Day 0 and up to lactation Day 21. Dose-dependent decrease in maternal body weights and food intake both during gestation and lactation in association with hepatic and renal toxicity was observed in dams exposed to 1000 mg/kg/day of acetaminophen. These changes were associated with higher post-implantation loss, lower litter size and live birth index. At 500 mg/kg/day dose-dependent decrease in maternal body weights and food intake were observed during gestation and lactation, but these changes were not associated with any changes in litter parameters evaluated. The administration of Liv.52 formulation did not induce any toxic effects during embryogenesis and postnatal development. However, co-administration of Liv.52 (1000 mg/kg/day) with acetaminophen induced partial or complete reversal of acetaminophen induced developmental toxic effects. In summary, Liv.52 an herbal hepato-protective formulation shown a significant protection against acetaminophen induced developmental toxicity in Wistar rats.